1999
DOI: 10.1093/alcalc/34.1.59
|View full text |Cite
|
Sign up to set email alerts
|

Urban-rural comparisons of drink-driving behaviour among late teens: a preliminary investigation

Abstract: -A preliminary study was conducted to examine the nature and extent of urban-rural differences in self-reported drinking and driving among youths in Western Australia. A total of 102 youths aged 17, 18 and 19 years were surveyed via a random street sampling technique about their alcohol consumption and drink-driving behaviour. Analyses indicated that urban youths had a significantly higher level of self-reported drink-driving behaviour than their rural counterparts. Males indicated a higher level of self-repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 14 publications
1
5
0
1
Order By: Relevance
“…Injuries and violence seem predominant risk behaviours. 9,10 Suicidal tendencies and depression are giving way to the newer phenomena of Injuries and violence. 11 It is indeed a worrisome situation.…”
Section: Discussionmentioning
confidence: 99%
“…Injuries and violence seem predominant risk behaviours. 9,10 Suicidal tendencies and depression are giving way to the newer phenomena of Injuries and violence. 11 It is indeed a worrisome situation.…”
Section: Discussionmentioning
confidence: 99%
“…For example, young rural drivers consider speeding on rural roads an acceptable, controllable risk (Knight et al 2013). However, most studies comparing risk perception between urban and rural environments have used between-subject comparisons (Dunsire and Baldwin 1999;Leadbeater et al 2008;Nordjaern et al 2010), effectively comparing rural and urban drivers, rather than environments. Within-subject comparisons of urban and rural driving environments are therefore required to provide more sensitive analysis (Streff and Geller 1988).…”
Section: Environmental Differences In Risk Perceptionmentioning
confidence: 99%
“…31,32 In addition, an early study in Western Australia, using face to face interviews, found young metropolitan residents were more likely than young rural residents to drink-drive. 21 However, given the length of time since these studies were conducted and the self-report nature of the data, these studies are likely to underreport drink driving prevalence in the community.…”
Section: Drink Drivingmentioning
confidence: 99%